Influence of Caring and Empathy on Students' Multiculturalism Mediated by Christianity: Role of University Core Values - Wenardjo, Elia; Panggabean, Hana (UI Scholars Hub, 2021)
Urban diversity is a reality for young people living in megacities such as Jakarta. Diversity in urban areas has its benefits; for example, it is a driver of creativity and innovation, but this urban diversity is vulnerable to intergroup friction and conflict. Therefore, urban youth needs to have a sense of multiculturalism, that is, an open attitude and respect for differences. Strong connections between Multiculturalism and Empathy as well as between Multiculturalism and spirituality or religiosity have been recognized. Universities that implement religious-oriented values and openness toward diversity are more likely to promote student multiculturalism. Based on literature, our study examines the influence of the organizational core values of Christianity and Caring as well as an additional social skill variable of Empathy on Multiculturalism among students in a Catholic university in Jakarta. We hypothesize that Multiculturalism is predicted by Caring and Empathy mediated by Christianity. This research was conducted with 155 bachelor students at University X. Research instruments comprised Organizational Core Value questionnaires, the Baron-Cohen and Wheelwright’s Empathy Quotient, and the Universal-Diverse Orientation Scale. Data were analyzed using the path analysis technique. The results show that Multiculturalism is predicted by Caring and Empathy mediated by Christianity. Christianity influences Multiculturalism. Each of Caring and Empathy influences Multiculturalism with the mediation of Christianity. These results suggest that a university might cultivate Multiculturalism by thoughtfully channeling religiously oriented values and a sense of Caring and Empathy in building university culture.